Penerapan Model Pembelajaran Project Based Learning Melalui Kegiatan Membuat Ecobrick Untuk Meningkatkan Kesadaran Peduli Lingkungan Siswa - Andi Wira Sakti Jaya; Erma Suryani Sahabuddin; Muhammad Irfan (JURNAL DIKDAS, 2025)
The problem addressed in this research is the lack of environmental concern among students at SD Inpres Parangbobbo. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through observations and documentation. The results indicate that the implementation of the Project Based Learning model through Ecobrick making activities effectively enhances environmental awareness among fifth-grade students. This is evidenced by the improvement in both teacher activity, student learning activities and environmental awareness. In Cycle I (Meetings I and II), teacher activity was categorized as sufficient and good, with percentages of 57% and 71%, respectively. This improved in Cycle II (Meetings I and II) to a very good category at 85%. Meanwhile, in Cycle I (Meetings I and II), student learning activity was categorized as sufficient and good, with percentages of 68% and 73%, averaging 71%. This also improved in Cycle II (Meetings I and II) to good and very good categories, with percentages of 83% and 91%, averaging 87%. In Cycle I (Meetings I and II), the environmental awareness of the students was categorized as low and sufficient, with percentages of 53% and 70%, resulting in an average of 61%. This then improved in Cycle II (Meetings I and II), where it was categorized as good and very good, with percentages of 83% and 92%, resulting in an average of 87%.